Improving Taxpayer Service and Facilitating Compliance in Singapore - Bird, Richard M. (World Bank, Washington, DC, 2012)
Over the past ten years, the government of Singapore has sought to modernize and computerize Singapore. Tax administration was one area of public administration that clearly required modernization. In 1992 the Inland Revenue Authority of Singapore (IRAS) was created to administer income and property taxes and a new value added tax called the Goods and Services Tax. Planning began to develop an integrated, computerized approach tax administration, which was soon reorganized on functional lines. This process has had made impressive results. In a survey, 95 percent of individual taxpayers, 83 percent of corporate taxpayers, and 93 percent of goods and services taxpayers said they were satisfied with IRAS services. This note discusses what Singapore has done to improve the taxpayer service and how it was done.